Optimalisasi abandon The Ship Drill Diatas KM BIntan Utama Dalam Upaya Peningkatan Keselamatan Pelayaran - Maulana Alghivary; Kuncowati; Nyoman Ardiana (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2025)
This study analyzes the implementation and optimization of the “Abandon the Ship Drill” aboard KM. Bintan Utama to enhance maritime safety. The research examines the effectiveness of the drill, crew readiness, procedural compliance, communication, and encountered obstacles. The study employed observation, interviews, and documentation methods. The results indicate a good level of compliance with standard operating procedures (85%) and full utilization of lifeboats (100%). However, communication barriers (30%) and inconsistencies in the use of life jackets (90%) were identified. Mental preparedness of the crew and the frequency of drills require improvement. Recommendations include enhanced training programs, improved communication exercises, and continuous evaluation to optimize maritime safety.